Empowerment of iqro park ’movement towards spiritual and physical health in school age children in Bangun Rejo Village, Tanjung Morawa District - Rochadi, R Kintoko; Hiswani (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Reading is one of HDI's indicators, UNDP categorizes Indonesia in 2017 is one of the countries with HDI 116 from 189 countries, under Philipina ranked 113. Governments and communities should pay more attention to the phenomenon of interest and reading cultures in Indonesia. In the village of Banjar Negoro B, Beringin District of Deli Serdang Regency has a group called Taman Iqro’ which is organised by the local community. In this area there are many residents who can not read the Koran write because of the economic limitation of parents. Based on the background above, it is necessary for devotion to increase reading interest and PHBS to healthy spiritual physical to the participants of Taman Iqro' especially in school age children. Method in devotion begins with socialization of the activities of devotion to the caretaker Taman Iqro'. Further introduction and training on how to improve reading interest and PHBS on the participants of Taman Iqro’ specially school age children. Training is conducted by lecture methods, video with LCD tools, discussion, question and answer for an introduction to how to improve reading interest and PHBS. The team of devotion also facilitates bookshelf, religious books and carpets to develop the intention of reading children's writing school in the village of Banjar Negoro B Deli Serdang Regency.